Factors influencing community reintegration of persons with spinal cord injury who received private inpatient rehabilitation in Gauteng - Van der Veen, Dale Anne (My University, 2018)
Persons with spinal cord injury (SCI) continue to face numerous contextual barriers to community reintegration, despite receiving rehabilitation. To ascertain the perceived factors influencing community reintegration of persons with SCI, who received private in-patient rehabilitation, a quantitative descriptive approach was used. Fifty-four persons participated in this study by completing a cross-sectional online self-administered survey, including; a sociodemographic profile, the Reintegrated into Normal Living Index (RNLI) and the Craig Hospital Inventory of Environmental Factors – Short Form (CHIEF–SF). Data was analysed using STATISTICA 13.2. Majority (63.5%) of participants were male, living with incomplete paraplegia (75%a) and 52% were employed. Eighty percent of participants experienced moderate to severe restrictions to participation, with low satisfaction in community reintegration. Help at work/school, business policies, help at home, attitudes at work/school and the natural environment were the greatest environmental barriers, while social support and access to private transport were the greatest facilitators to community reintegration.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Occupational Therapy. Johannesburg, 2018.
Keywords: Community Reintegration; Spinal Cord Injuries; Rehabilitation